2008
DOI: 10.1021/nl080524d
|View full text |Cite
|
Sign up to set email alerts
|

Large Anisotropy of Electrical Properties in Layer-Structured In2Se3 Nanowires

Abstract: Layer-structured indium selenide (In 2Se 3) nanowires (NWs) have large anisotropy in both shape and bonding. In 2Se 3 NWs show two types of growth directions: [11-20] along the layers and [0001] perpendicular to the layers. We have developed a powerful technique combining high-resolution transmission electron microscopy (HRTEM) investigation with single NW electrical transport measurement, which allows us to correlate directly the electrical properties and structure of the same individual NWs. The NW devices w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
127
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(134 citation statements)
references
References 35 publications
6
127
0
Order By: Relevance
“…As a result, nanoribbons have a rectangular cross section. TEM studies on a wide nanoribbon ( Figure 2B) reveal similar crystalline characteristics to the narrow nanoribbon ( Figure 2A); it grows along [11][12][13][14][15][16][17][18][19][20] direction as well. The TEM data of a nanowire with rough surface are shown in Figure 2C.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…As a result, nanoribbons have a rectangular cross section. TEM studies on a wide nanoribbon ( Figure 2B) reveal similar crystalline characteristics to the narrow nanoribbon ( Figure 2A); it grows along [11][12][13][14][15][16][17][18][19][20] direction as well. The TEM data of a nanowire with rough surface are shown in Figure 2C.…”
mentioning
confidence: 76%
“…Nanowires, which exhibit rough surfaces, are formed by stacking nanoplatelets along the axial direction of the wires. Nanoribbons are grown along [11][12][13][14][15][16][17][18][19][20] direction with a rectangular crosssection and have diverse morphologies, including quasi-one-dimensional, sheetlike, zigzag and sawtooth shapes. Scanning tunneling microscopy (STM) studies on nanoribbons show atomically smooth surfaces with 1 nm step edges, indicating single Se-Bi-Se-Bi-Se quintuple layers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] By controlling the synthesis parameters or thermal/electrical pretreatment processes, several phases (superlattice, simple hexagonal -phase, simple hexagonal -phase, and amorphous state) with vastly different electrical conductivity can coexist at the ambient condition, [12][13][14] which explains the research interest of In2Se3 as a prototypical phasechange material. 7,[12][13][14][15][16][17][18] In addition, the lattice constant of In2Se3 matches well with Bi2Se3, which is heavily investigated for its high thermoelectric figure-of-merit and topological insulator nature. 19,20 The chemical and structural compatibility between the two chalcogenides enables the growth of In2Se3/Bi2Se3 heterostructures.…”
mentioning
confidence: 99%
“…It has been previously reported that pristine VLS-grown [11][12][13][14][15][16][17][18][19][20] In 2 Se 3 nanoribbons with superlattice structures (Fig. 3a, left) exhibit metallic behavior and room temperature R 2T as low as kilo-ohms 10 . Further studies show that after applying a low voltage (<1V) pulse, R 2T can increase up to mega-ohms and the ribbons behave semiconducting.…”
mentioning
confidence: 99%